Immune-Mediated Metabolic Kynurenine Pathways Are Involved in the Postoperative Cognitive Dysfunction after Cardiopulmonary Bypass - Yi, Shuang Qiang; Yang, Mi; Duan, Kai Ming (The Thoracic and Cardiovascular Surgeon, 2015)
Postoperative cognitive dysfunction (POCD) after cardiopulmonary bypass is a serious complication that can lead to personality changes, memory loss, reduction in the ability to learn, and other central nervous system dysfunctions. In recent years, there have been improvements in measures to protect the brain during surgery, although the incidence of cognitive dysfunction after cardiac surgery remains high (33 to 83% short-term and 20 to 60% long-term cognitive dysfunction). Despite the large amount of basic and clinical research on the incidence of POCD, its exact pathogenesis and complexity are not clear. Many studies have shown that the kynurenine pathway (KP) and cognitive function in humans are closely related. Some reports also show that the imbalance of some metabolites of the KP such as kynurenic acid and quinolinic acid (QUIN), which act in dynamic equilibrium under physiologic conditions, have effects on the central nervous system and can significantly affect cognitive function. Further studies have shown that inflammatory mediators may act on key enzymes of the KP causing KP-induced disorders. Severe inflammatory reaction occurs in patients undergoing cardiopulmonary bypass, which triggers metabolic pathways that are closely related to changes in cognitive function. In this review, we summarize that inflammation-induced metabolic kynurenine (KYN) pathway disorders are likely to have an important role in incidence of POCD after CPB surgery.
Keywords: cardiopulmonary bypass; CBP; systemic inflammation; immunology; KP